Evaluation of the effects of a pre-school intervention on literacy development in children - Evangelou, M (2001)
This short-term longitudinal study investigates the effects of the 'Peers Early Education Partnership' (PEEP), a pre-school intervention in Oxfordshire, which aims to increase the educational achievement (especially literacy skills) of disadvantaged children from infancy to 5 years. PEEP strives to form partnerships with parents and carers by recognising and supporting their contribution to children’s learning during their formative pre-school years. The study evaluated the effects of the PEEP Project over the year following children's entry at age 3. The study aimed to observe closely, at a micro level, what effects the PEEP programme had upon children's development. Based on a comparison with children without PEEP experience, the study looked particularly, first, at how the PEEP parent education programme affected the literacy and numeracy development of children and, second, whether there was a difference one year later in children's self-esteem and social-emotional development. The method was a quasi-experimental design, which included pre- and post-testing measures. In order to assess the outcomes of the PEEP intervention on children's cognitive, language and social-emotional development, standardised tests and educational tasks were administered to the children at the start of the intervention and after one year. The same assessments were applied to the 'intervention' and 'comparison' children. The sample consisted of 160 children and their families. Seventy-three of these children attended the intervention in the PEEP catchment area in Oxfordshire while their parents attended weekly group sessions. A comparison group of 87 children were recruited from five playgroups in a nearby town also in Oxfordshire, matched for age and social characteristics with their Oxford counterparts. Neither the children in the comparison group, nor their parents, attended any PEEP group sessions. Children in the PEEP group had significant gains in the following areas of development: Language and Literacy (Verbal Comprehension, Vocabulary, Phonological Awareness, Concepts about Print, Writing), Numeracy (Early Number Concepts) and Self-esteem (Maternal Acceptance)